Case series and review of emergency front‐of‐neck surgical airways from The Australian and New Zealand Emergency Department Airway Registry. (11th November 2020) - Alkhouri, Hatem; Richards, Clare; Miers, James; Fogg, Toby; McCarthy, Sally
Abstract: Background: An emergency front‐of‐neck access (eFONA), also called can't intubate, can't oxygenate (CICO) rescue, is a rare event. Little is known about the performance of surgical or percutaneous airways in EDs across Australia and New Zealand. Objective: To describe the management of cases resulting in an eFONA, and recorded in The Australian and New Zealand Emergency Department Airway Registry (ANZEDAR). Methods: A retrospective case series and review of ED patients undergoing surgical or percutaneous airways. Data were collected prospectively over 60 months between 2010 and 2015 from 44 participating EDs. Results: An eFONA/CICO rescue airway was performed on 15 adult patients: 14 cricothyroidotomies (0.3% of registry intubations) and one tracheostomy. The indication for intubation was 60% trauma and 40% medical aetiologies. The intubator specialty was emergency medicine in eight (53.3%) episodes. Thirteen (86.7%) cricothyroidotomies and the sole tracheostomy (6.7%) were performed at major referral hospitals with 12 (80%) surgical airways out of hours. In four (26.7%) cases, cricothyroidotomy was performed as the primary intubation method. Pre‐oxygenation techniques were used in 14 (93.3%) episodes; apnoeic oxygenation in four (26.7%). Conclusions: Most cases demonstrated deviations from standard difficult airway practice, which may have increased the likelihood of performance of a surgical airway, and its increased likelihood out of hours. Our findings may inform training strategies to improve care for ED patients requiring this critical intervention. We recommend further discussion of proposed standard terminology for emergency surgical or percutaneous airways, to facilitate clear crisis communication. Abstract : This is the first descriptive study of emergency front of neck surgical access (eFONA) airway management in Australian and New Zealand EDs. The eFONA rate reported of 0.31% is consistent with international data. Only 47% of eFONA airways had a typical indication for potentially needing surgical access.